Analysis of the Implementation of Self Assessment System increasing Awareness of Tax Paying Compliance in Manado City (Study at Manado City Regional Revenue Agency) - Tamin, Zefanya Evangeline; Elim, Inggriani; Wangkar, Anneke (ACCOUNTABILITY, 2024)
Self assessment system is a tax collection system that authorizes taxpayers to determine the amount of tax payable in accordance with applicable laws and regulations. This study aims to analyze the application of the self assessment system in increasing awareness of compliance in paying hotel taxes, restaurant taxes, entertainment taxes, and in increasing regional tax revenues at the Manado City Regional Revenue Agency. The analysis method used in this thesis research is a descriptive method. The type of research used is qualitative descriptive. The results of the research on the realization of tax reporting using the self assessment system at the Manado City Regional Revenue Agency in 2022 showed that the tax revenue was IDR.292,254,150,326.53 from the tax revenue target of IDR 317,748,750,000.00. The percentage of tax compliance achieved by the Manado City Regional Revenue Agency in 2022-2023 reached 91.97%. As well as the percentage achieved based on the number of taxpayers registered and paying reaches 100% based on this data, the implementation of the selfassessment system is included in the very high category in increasing awareness of tax compliance and in increasing revenue at the Manado City Regional Revenue Agency. Keywords: Analysis, Self Assessment System, Compliance.